UNA NIÑA QUE, SIN PIES, VOLABA: CRÍTICA LITERARIA FEMINISTA DE UNA NOVELA DE ROSARIO AGUILAR - Gamboa Barboza, Isabel (2008)
This paper analyzes the novel “La niña blanca y los pájaros sin pies” (The white girl and the feetless birds) of Nicaraguan author Rosario Aguilar, from a feminist non essentialist perspective. It proposes that, despite the author’s conscious intentions, its construction of different types of women who comply, but also transcend the sexist stereotypes mandated for them, makes this novel a strong example, of how to re-write the official historical discourse on the Spanish “conquest” merely by envisioning the role played in it by women, but also through the deconstruction of those female stereotypes into a variety of contradictory characters, in a world that despises them.